RISK FACTORS OF HIGH INTRACRANIAL PRESSURE AND THE RELATED OUTCOMES IN SUBJECTS WITH SEVERE HEAD INJURY IN SANGLAH GENERAL HOSPITAL DENPASAR - Wayan Niryana (Indoscholar, 2018)
Background: Severe head injury management target is to prevent the secondary brain injury characterized by deterioration in the outcome. High intracranial pressure (ICP) and low cerebral perfusion pressure (CPP) could cause unfavourable outcomes which is influenced by many factors, such as hypoxia and haemorrhage lesions pictured on head CT scan. This study analyzes various risk factors that can lead to increased ICP and the influence of high ICP on the outcome. Methods: This study is a prospective cohort, involving 42 consecutive subjects with severe head injury patients from June to October 2016. The subjects underwent examination for blood pressure, blood gas analysis, and head CT scan. ICP monitoring was then performed and the outcome was assessed using the Glasgow Outcome Scale score when the patient was discharged. In this study, risk factors such as hypoxia, hypotension, and subarachnoid haemorrhage (SAH) were analyzed. Statistical analysis was performed with SPSS 27 with a confidence interval of 95%. Result: There were two risk factors that significantly influenced the increase of ICP, which were hypotension (RR 0.27; 95CI 0.095-0.775; p<0.001) and hypoxia (RR 0.125; 95CI 0.034-0.457; p<0.001). High ICP value ≥ 20 mmHg was associated with an unfavourable outcome (RR 2.28; 95CI 1.31-3.98; p<0.001). Conclusion: Hypoxia and hypotension were two risk factors that significantly influenced the increase of ICP, where high ICP caused the unfavourable outcome.